2009
DOI: 10.1166/jnn.2009.1576
|View full text |Cite
|
Sign up to set email alerts
|

Non-Specific Adsorption of Streptavidin on Single Walled Carbon Nanotubes

Abstract: We report the semi quantitative determination of the non specific adsorption of streptavidin onto raw and functionalized single walled nanotubes (SWNTs) using different approaches. SWNTs were covalently functionalized with carboxylated groups, amine groups and polyethylene glycol (PEG), and non-covalently functionalized with polyethylene glycol, Pluronic F-127 and Tween20. SWNTs covalent functionalization has been carried out through oxidation and acyl chloride formation. The non covalent functionalization was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…This was a consequence of the full coverage of the CNTs in the devices in streptavidin (see Figure 4) which prevented other biomolecules from being able to be absorbed on the CNT surface. As previously reported by the authors, 33 covalent and noncovalent modification of SWCNTs with polymers, surfactants, and functional groups is not capable of preventing the absorption of streptavidin. Likewise, the anchoring of a polymer was capable of preventing the aggregation of DNA in the electrodes changing the Schotky barrier, 52 but it was not successful in preventing the absorption of streptavidin.…”
Section: ■ Results and Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This was a consequence of the full coverage of the CNTs in the devices in streptavidin (see Figure 4) which prevented other biomolecules from being able to be absorbed on the CNT surface. As previously reported by the authors, 33 covalent and noncovalent modification of SWCNTs with polymers, surfactants, and functional groups is not capable of preventing the absorption of streptavidin. Likewise, the anchoring of a polymer was capable of preventing the aggregation of DNA in the electrodes changing the Schotky barrier, 52 but it was not successful in preventing the absorption of streptavidin.…”
Section: ■ Results and Discussionsupporting
confidence: 58%
“…They found that the modified SWNTs were resistant to proteins such as streptavidin, avidin, bovine serum albumin, glucosidase, and staphylococcal protein A. The authors 33 tested different strategies, trying unsuccessfully to prevent nonspecific adsorption of streptavidin on SWNTs. The hydrophobic character of the SWNTs was modified by surface functionalization with oxygenated groups, amine groups, and PEG, which rendered the SWNTs surface more hydrophilic.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The objective of using the polymer was to avoid an aggregation of antibodies on the electrodes that could modify the metal work function and the Schottky barrier and also to prevent the nonspecific adsorption of proteins and biomolecules on the CNTFET. Strong binding between the nanotubes and proteins has been reported by several authors. , This is an important issue when the detection is carried out in a serum environment.…”
mentioning
confidence: 95%